TEKNIK TERJEMAHAN UNTUK PENERJEMAHAN LIRIK LAGU MAHER ZAIN - Nur Laili Yusuf (Mastery: Master of English Language Journal, 2024)
This study aims to examine the translation procedures employed by a translator in translating Maher Zain's song lyrics from English to Indonesian. This study specifically examines Maher Zain's selected song lyrics due to its translation popularity in Indonesia. The study utilized the descriptive qualitative method based on Vinay and Darbelnet's theory. The researcher has identified several procedures used by translators are modulation, transposition, equivalence, and borrowing. In translating the selected Maher Zain’s song lyrics, 105 data were found. 25 data were translated using the transposition procedure, 55 data used the modulation procedure, 10 data used the equivalence procedure. Finally, it has been found that translators used 15 data double translation procedures, namely borrowing and equivalence.